Quotations for Speeches - Ed. Daintith, John (Bloomsbury Publishing Plc, 1992)
Taken from sources as diverse as Diana, Princess of Wales to the Bible, this guide contains over 1000 quotations to heighten or illustrate any speech. The guide is arranged into over 200 themes plus name and keyword searches which make it accessible and easy-to-use.
Keywords: English-Speeches-Quotations-Non fiction